(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Acinetobacter baumannii (Ab) is developing resistance to a variety of common antibiotics. and become multidrug resistant, extreme drug resistant, and pan drug resistant pathogens, requiring the identification of new antibiotics as well as the identification of new plant compounds capable of acting against Ab. Recent research has revealed MDR Ab co-infections with COVID-19, raising alarm bells. Since its isolation, Usnic acid has been investigated for a variety of pharmacological activities, including antioxidant, antitumor, antibacterial, antifungal, antiviral, antiprotozoal, and insecticidal. Many Plant-derived drugs show promising activity as new antimicrobial agents against multidrug resistant (MDR) strains. There is insufficient data to support the antibacterial activity of (+)-UA against MDR Acinetobacter baumannii..